2020
DOI: 10.11591/ijeecs.v20.i1.pp385-394
|View full text |Cite
|
Sign up to set email alerts
|

Image encryption scheme in public key cryptography based on cubic pells quadratic case

Abstract: Cryptography systems face new threats with the transformation of time and technology. Each innovation tries to contest challenges posed by the previous system by analyzing approaches that are able to provide impressive outcomes. The prime aim of this work is to urge ways in which the concept of Pell’s equation can be used in Public key Cryptography techniques.The main aim of this approach is secure and can be computed very fast. Using Cubic Pell’s equation defined in Quadratic Case, a secure public key techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Consequently, the experimental results have been demonstrated that it is difficult to discover the used key. Figure 3 explains the cryptosystem of the algorithm has been divided into two modules [28], [29], which are; i) data encryption module and ii) data decryption module.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the experimental results have been demonstrated that it is difficult to discover the used key. Figure 3 explains the cryptosystem of the algorithm has been divided into two modules [28], [29], which are; i) data encryption module and ii) data decryption module.…”
Section: Methodsmentioning
confidence: 99%
“…Where 𝐶 𝑗 (𝑡) is the cost function of the jth node at the iteration instant of t. 𝐶 𝑗 𝑤𝑜𝑟𝑠𝑒 (𝑡) represents the worst cost function and 𝐶 𝑗 𝑏𝑒𝑠𝑡 (𝑡) represents the best cost function. The mass and acceleration of the jth node are given by ( 10) and (11).…”
Section: Gravitational Search Algorithmmentioning
confidence: 99%
“…The public keys are distributed to all people, and only the person who is participating in the conversation recognizes the private key. ECC, unlike secret key cryptography, is ideal for systems where a protected channel to relay the private key is not available [11], [12]. ECC is a nearly modern public key cryptosystem that offers higher thresholds, lower mathematical difficulty, smaller key sizes, and greater computational efficiency [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further, they analyzed cryptanalysis of Fermat's attack [28,29], Weiner's continued fraction [30] and extended Euclidean method and these are compared along with RSA using numerical examples. A novel public key cryptography technique is proposed by R a g h u n a n d a n et al [31] which makes use of using Pell's quadratic case for key generation process and these are compared along with RSA using numerical examples. R a g h u n a n d a n et al [32] also introduces the concept of fake modulus which is to overcome the limitations of Integer factorization attack.…”
Section: Rsa Variantsmentioning
confidence: 99%